Optimalisasi Strategi Pemasaran Melalui Analisis SWOT (Studi Kasus Adlya Olshop Dalam Meningkatkan Penjualan) - Meriyana, Meriyana (PENG: Jurnal Ekonomi dan Manajemen, 2025)
In an increasingly competitive digital era, e-commerce businesses such as Adlya Olshop face challenges in increasing sales and expanding market share. Digital transformation has changed consumer behavior, who now prefer a personalized and interactive online shopping experience. Even though Adlya Olshop has implemented various marketing strategies, including promotions on social media and attractive discounts, the presence of new competitors with aggressive strategies demands further innovation. This research uses a qualitative approach to explore business owners' perspectives regarding the challenges and marketing strategies implemented. Primary data was obtained through in-depth interviews, while secondary data was taken from existing sources. Through SWOT analysis, this research identifies the strengths, weaknesses, opportunities and threats faced by Adlya Olshop. The results show that by utilizing technology such as artificial intelligence (AI) and data analytics, as well as developing interactions on social media, Adlya Olshop can increase operational efficiency and relevance in the market. With an inclusive and community empowerment-oriented approach, Adlya Olshop not only has the potential to achieve financial success, but also contribute to the welfare of local communities, making it an example of a sustainable business in the e- commerce era. Several suggestions that can be given to improve Adlya Olshop's performance include improving training for resellers, optimizing social media, carrying out continuous product innovation, implementing a customer loyalty program, creating a proactive feedback system, conducting regular market analysis, strengthening the brand community, and diversifying. distribution channels.